Understanding the Relationship of Conflict, Psychological safety, and Success in Software Development Projects - Farias, Wladimir; Silva, Brenda; Lencastre, Maria; Fagundes, Roberta (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3607, 2024)
Software development involves complex socio-technical activities with common conflicts arising from human and non-human factors. However, the impact of these conflicts, particularly non-human ones, on project success still needs to be investigated. Psychological safety is a key to mitigating these conflicts. In this paper, we aim to understand how conflicts and psychological safety impact the success of software development projects—considering the categorization of conflicts into human-rooted (HRC) and non-human-rooted (NHRC) and examining organization size, team size, and psychological safety as moderating factors. To achieve our goal, we replicated an existing study in the area and included new hypotheses; we also adapted the surveys to Portuguese, used a structured survey to collect data, and applied structural equation modeling for the analysis. The results include the reception of 155 responses and show that human-rooted conflict strongly negatively impacts software project success, regardless of organization or team size. Non-human-rooted conflict positively affects project success only in corporations (> 100 employees) but negatively impacts small and medium-sized organizations (< 100 employees). While not directly correlated with project success, psychological safety appears as a crucial moderating factor.